2013
DOI: 10.4161/pri.24239
|View full text |Cite
|
Sign up to set email alerts
|

Amyloidogenic peptide homologous to fragment 129–148 of human myocilin

Abstract: Amyloidogenic peptide homologous to fragment 129-148 of human myocilin, Prion, 7:3, 248-253,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…We analyzed the primary structure of the NSP7 protein using three programs – Arches, which allows predicting the formation of hairpins characteristic of amyloid-like proteins [18], FoldAmyloid [19], which analyzes the local amino acid composition, and an original program for searching for mirror symmetry motifs [23]. The choice of these programs was due to the fact that in the course of our previous studies, the programs separately made it possible to predict amyloidogenic peptides [24][25][26]. Figure 1 shows the results of the search for potential amyloidogenic regions in NSP7.…”
Section: Resultsmentioning
confidence: 99%
“…We analyzed the primary structure of the NSP7 protein using three programs – Arches, which allows predicting the formation of hairpins characteristic of amyloid-like proteins [18], FoldAmyloid [19], which analyzes the local amino acid composition, and an original program for searching for mirror symmetry motifs [23]. The choice of these programs was due to the fact that in the course of our previous studies, the programs separately made it possible to predict amyloidogenic peptides [24][25][26]. Figure 1 shows the results of the search for potential amyloidogenic regions in NSP7.…”
Section: Resultsmentioning
confidence: 99%
“…The role of repeats in fibrillogenesis has been shown for the prion protein PrP [ 20 ] and for alpha-synuclein [ 21 ]. The leucine zipper motif located within myocilin usually forms an alpha-helix structure but is also prone to fibrillogenesis even under normal physiological conditions [ 22 ]. It would appear that the presence of easily identifiable repetitive sequences in these proteins is evidence of their relatively recent evolutionary origin [ 23 ].…”
Section: The Role Of Primary Structure Motifs In Conformational Trmentioning
confidence: 99%
“…Amyloid fibril formation is a common phenomenon in human pathology. 1 Recent studies have shown that certain diseases such as hereditary glaucoma 2,3 or influenza infection 4 include a stage of amyloid-like oligomerization and amyloid fibril formation. A universal strategy for amyloidosis treatment currently has still yet to be developed.…”
Section: Introductionmentioning
confidence: 99%